The Treaty of Aachen of 2019: Opportunities to strengthen Franco-German cooperation on sustainable development - Laura-Theresa Krüger; Julie Vaillé (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
On 22 January 2019, France and Germany signed the Aachen Treaty. Therein, 56 years after the Elysée Treaty, re-emphasising their support for multilateralism, sustainable development and development cooperation. Despite the ambitions expressed in this document, the signing of the Treaty calls for reflection: to what extent does this type of agreement indeed lead to joint operational approaches and have a real impact on French-German cooperation? To answer this question, this Briefing Paper analyses the obstacles to a closer French-German cooperation in the field of sustainable international development. It focuses on how these commitments are put into practice at the level of political coordination and project implementation. The analysis is based on about 20 interviews with representatives of French and German ministries, development agencies and think tanks. It finds that things get most complicated at the level of political coordination. Three main obstacles are identified: slightly diverging strategic visions; an incompatibility between institutional structures concerning the degree of specialisation and the mandates of the ministries responsible for steering aid, as well as the degree to which development agencies are involved in strategic decision-making; and cultural particularities regarding communication and time management. Five recommendations are proposed: Protect what has been achieved: the alignment between France and Germany at the political and project implementation levels is an asset in an international context where the focus on national interests is increasing. Such cooperation should thus continue to be supported and reinforced. Channel the political momentum to the working level: in order to reinforce their coordination, the two countries could establish a solid and regular follow-up mechanism for each commitment, detailing joint actions, shared objectives and milestones. Promote mutual knowledge and trust: personnel exchange between the departments, as well as deep dive sessions on the two countries' activities and strategies would allow increased understanding of each other. Share best practices: a balanced and respectful French-German collaboration could be encouraged by the sharing of practices for which one country is more advanced or better positioned than the other (such as the French interministerial coordination or the German project evaluation and monitoring procedures). Act jointly or divide the work: in the run-up to each joint Franco-German action, make a deliberate and conscious decision whether the two countries have an interest to act jointly or to divide the work. This decision would allow maximisation of the impact, either by specialising or by working together.
Keywords: 330